Effectiveness and Safety of Rituximab for Refractory Myasthenia Gravis: A Systematic Review and Single-Arm Meta-Analysis - Zhao, Cong; Pu, Meng; Chen, Dawei; Shi, Jin; Li, Zhuyi; Guo, Jun; Zhang, Guangyun (Frontiers in Neurology, 2021)
Background and objective: Myasthenia gravis (MG) is an autoimmune neuromuscular disease. Nearly 10-30% of patients with MG are refractory to conventional therapy. Rituximab (RTX), a monoclonal antibody targeting CD20, is increasingly used in autoimmune disorders. We performed a systemic review and meta-analysis to evaluate the effectiveness and safety of RTX for refractory MG. Methods: Studies published between January 1, 2000 and January 17, 2021 were searched in PubMed, EMBASE, Cochrane Library and ClincalTrails.gov. Primary outcomes included proportion of patients achieving minimal manifestation status (MMS) or better and quantitative MG (QMG) score change from baseline. Secondary outcomes were glucocorticoids (GC) doses change from baseline and proportion of patients discontinuing oral immunosuppressants. Results: A total of 24 studies involving 417 patients were included in the meta-analysis. An overall 64% (95% confidence interval, 49%-77%) of patients achieved MMS or better. The estimated reduction of QMG score was 1.55 (95% confidence interval, 0.88-2.22). The mean reduction of GC doses was 1.46 (95% confidence interval, 1.10-1.82). The proportion of patients discontinuing oral immunosuppressants was 81% (95% confidence interval, 66-93%). Subgroup analyses showed that the proportion of patients achieving MMS or better and discontinuing oral immunosuppressants was higher in MuSK-MG group than those in AChR-MG group. Improvement was more pronounced in patients with mild to moderate MG compared to those with severe MG. Moreover, the efficacy appeared to be independent of the dose of RTX. 19.6% of patients experienced adverse events, most of which was mild to moderate. Only one patient developed progressive multifocal leukoencephalopathy. Conclusions: RTX can alleviate the symptom of weakness, decrease QMG score and reduce the doses of steroids and non-steroid immunosuppressive agents in refractory MG. It is well tolerated with few severe adverse events. Randomized controlled trials are urgently needed to study the efficacy of RTX in treating refractory MG and to identify the characteristics of patients who might respond well to RTX.